2022
DOI: 10.3329/bjb.v51i3.61995
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Surrogates For Drought Resilience In Temperate Maize (Zea Mays L.)

Abstract: Drought is one of the major constraints affecting the economic yield of maize worldwide. Present study was carried out to select the surrogates for drought resilience in 70 maize landraces collected from diverse agro-ecologies of Kashmir Himalayas. Significant variation was observed among the genotypes for all the traits under well-watered and drought conditions. Due to the drought stress, the highest reduction was observed for the canopy temperature (175.18%), followed by root volume (69.77%), top root biomas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Mallikarjuna et al [18] out of 135 genotypes evaluated, none of the genotypes showed resistant, 34 genotypes expressed moderately resistant reaction, 73 showed moderately susceptible reaction and 29 genotypes exhibited susceptibility reaction to TLB disease. Yousuf et al [1] confirmed that among seventy landraces, forty-three lines were categorised as resistant, eighteen moderately resistant, five moderately susceptible and landrace Tral 3 recorded highest percent disease index (PDI) as 78.91 per cent and rated as susceptible. Bantu et al [19] screened 70 medium maturing maize inbreds against TLB under artificial epiphytotic conditions.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Mallikarjuna et al [18] out of 135 genotypes evaluated, none of the genotypes showed resistant, 34 genotypes expressed moderately resistant reaction, 73 showed moderately susceptible reaction and 29 genotypes exhibited susceptibility reaction to TLB disease. Yousuf et al [1] confirmed that among seventy landraces, forty-three lines were categorised as resistant, eighteen moderately resistant, five moderately susceptible and landrace Tral 3 recorded highest percent disease index (PDI) as 78.91 per cent and rated as susceptible. Bantu et al [19] screened 70 medium maturing maize inbreds against TLB under artificial epiphytotic conditions.…”
Section: Resultsmentioning
confidence: 96%
“…"Maize with a notable productive potential among the cereals, is the third most important grain crop after wheat and rice" [1]. In India, it is cultivated over an area of 9.89 m ha with a production and productivity of 31.60 million tonnes and 3199 kg ha -1…”
Section: Introductionmentioning
confidence: 99%